Nanofiber-expanded stem cells mitigate liver fibrosis: Experimental study. Issue 5 (October 2016) - Salem, Neveen A.; Ahmed, Hanaa H.; Aglan, Hadeer A.; ElShebiney, Shaimaa A.
Highlights: MSCs expanded on nano fibers had prominent effect in the management of liver fibrosis. MSCs cultured on nanofibers maintained stable gene expression profile and functional biochemistry. Nanofiber mimiked the natural microenvironment and enhanced proliferation and differentiation of MSCs. Abstract: Objectives: This study examines a pretreatment strategy to strengthen the hepatic lineage divergence of mesenchymal stem cells (MSCs). Design and methods: BMSCs were expanded in the presence or absence of nanofiber (NF) and treated with growth factors (GF) prior to transplantation. Thioacetamide (TA) was used for liver fibrosis induction and transplantation of NF-expanded BMSCs was compared biochemically and histologically to the cells expanded without NF scaffold. Results: The ultraweb NF caused better proliferation and characterization of MSCs. MSCs transplantation significantly improved liver functions, increased hepatic HGF and Bcl-2 levels, whereas decreased serum fibronectin, hepatic TNF-α and TGF-β1 levels. Hepatic HNF4α, FOXa2, CYP7a1 genes expression were enhanced while β-5-Tub and AFP genes expression were depressed. Histological study documented these results. Differentiated NF-MSCs showed pronounced enhancement of the aforementioned parameters as compared to differentiated MSCs in the absence of NF. Conclusion: pretreatment with growth factors in the presence of NF augment homing, repopulation and hepatic differentiation abilities of MSCs and proves to be a promising approach for the treatment of liver fibrosis.